Diagnosis and management of a giant ovarian cyst in the gravid-puerperium period: a case report - Sibraogo Kiemtoré; Hyacinthe Zamané; Yobi Alexis Sawadogo; Rodrigue Sansan Sib; Evelyne Komboigo; Ali Ouédraogo; Blandine Bonané (BMC, 2019)
Abstract Background Giant ovarian cyst is very rare in gravid-puerperium period. It is a cause of a maternal-fetal morbidity. We report a case of a giant benign ovarian cyst in gravid-puerperium period which was diagnosed and managed in a hospital of a low-resource country. Case presentation Data were collected by historical review, clinical examination, laboratory investigations, imaging examination, and by histopathological study of the excised surgical specimen. It is the case of a 25-year-old woman who was third gravida and third para with unknown pathological history. After she had given birth through vagina, a giant ovarian cyst, unknown during pregnancy, was diagnosed. A left oophorectomy carrying the cyst was performed after laparotomy in Yalgado Ouedraogo University Hospital Center of Ouagadougou (Burkina Faso). The cyst was 42 cm long and weighed 19.7 kg. The histology of the operative specimen revealed serous cystadenoma of the ovary. The postoperative course was uneventful. Conclusion This case reports that vaginal delivery is possible with a giant ovarian cyst associated with pregnancy. Surgical management of the cyst can be performed in the postpartum with satisfaction.